2011
DOI: 10.1128/jvi.01875-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Functional Domains within the Arenavirus Nucleoprotein

Abstract: N-N) interactions was analyzed. We found that N protein displays two functional domains. By using coimmunoprecipitation studies, VLP incorporation assays, and double immunofluorescence staining, the carboxy-terminal region of N was found to be required for N-Z interaction and also necessary for incorporation of N protein into VLPs. Moreover, further analysis of this region showed that the integrity of a putative zinc-finger motif, as well as its amino-flanking sequence (residues 461 to 489), are critical for Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 63 publications
4
54
0
3
Order By: Relevance
“…Our studies demonstrated that TCRV NP is able to self-oligomerize with a yet undefined molecularity and identified the N-ter domain (residues 1 to 332) as being essential for NP self-interaction (11). Biochemical evidence supporting the relevance of the N-ter domain in self-association has also been reported for the NP of the OW arenaviruses lymphocytic choriomeningitis virus (LCMV) and LASV (24,25).…”
mentioning
confidence: 60%
See 4 more Smart Citations
“…Our studies demonstrated that TCRV NP is able to self-oligomerize with a yet undefined molecularity and identified the N-ter domain (residues 1 to 332) as being essential for NP self-interaction (11). Biochemical evidence supporting the relevance of the N-ter domain in self-association has also been reported for the NP of the OW arenaviruses lymphocytic choriomeningitis virus (LCMV) and LASV (24,25).…”
mentioning
confidence: 60%
“…Furthermore, a 28-residue region predicted to fold into an ␣-helix (helix 5) within the N-ter domain was identified as being essential to sustain TCRV NP self-association (11). However, the mechanism by which NP homo-oligomerization contributes to RNP assembly as well as to viral transcription and replication remains unclear.…”
Section: Effect Of N-terminal and C-terminal Mutations On Tcrv Np Selmentioning
confidence: 99%
See 3 more Smart Citations